Intertextuality in the tales of Rabbi Nahman of Bratslav : a close reading of Sippurey Maʼasiyot - Schleicher, Marianne. (Studies in the history of religions,, 2007)
Until 1806, Rabbi Nahman of Bratslav (1772-1810) disseminated his thoughts on redemption through homilies. In 1806, however, Nahman chose the genre of tales as an additional and innovative means of religious discourse. An academic close reading of all of the tales, known as Sippurey Ma'asiyot , has not yet been undertaken. As the first comprehensive scholarly work on the whole selection of tales and contrary to previous scholarship, this book does not reduce the tales to biographical expressions of Nahman's tormented soul and messianic aspirations. Instead, it treats them as religious literature where the concept of "intertextuality" is considered essential to explain how Nahman defines his theology of redemption and invites his listeners and readers to appropriate his religious world-view.